IMPROVING STUDENTS' VOCABULARY MASTERY THROUGH CARTOON FILM (A Study at the Sixth Grade Students of MIS Thoyyibatul Ulum Hutaimbaru in 2020/2021 Academic Year) - Nurhot Jamilah Dongoran (JURNAL LINER (Language Intelligence and Educational Research), 2021)
ABSTRACT Dongoran, Nurhot Jamilah. 2020. Improving Students’ Vocabulary Mastery through Cartoon Film (A Study at the Sixth Grade of MIS Thoyyibatul Ulum Hutaimbaru in 2020/2021 Academic Year). Skripsi. Program Studi Pendidikan Bahasa Inggris. Institut Pendidikan Tapanuli Selatan. The objectives of this research are to know: 1) The extent of students’ vocabulary mastery score before apply cartoon film at the sixth grade of MIS Thoyyibatul Ulum Hutaimbaru in 2020/2021 academic year. 2) The extent of the students’ vocabulary mastery score after apply cartoon film at the sixth grade of MIS Thoyyibatul Ulum Hutaimbaru in 2020/2021 academic year. 3) The extent of the improvement of using cartoon film on the students’ score of vocabulary mastery at the sixth grade of MIS Thoyyibatul Ulum Hutaimbaru in 2020/2021 academic year. The researcher using classroom action research which consists of two cycles and the subject of the research is the sixth grade of MIS Thoyyibatul Ulum Hutaimbaru which consists of 24 students. The instrument of the research was pre-test, post-test, observation checklist, and lesson plan. The result of the research is 1) The extent of the students’ vocabulary mastery score before apply cartoon film is still low and needs to improve. It can be seen from the students’ vocabulary mastery mean score in the pre-test is 69,37. 2) The extent of the students’ vocabulary mastery score after apply cartoon film is cartoon film can improve students’ vocabulary mastery. It can be seen from the students’ mean score of post-test in the first cycle is 76,25 While the mean score of post-test in the second cycle is 83,75 3) The extent of the improvement of using cartoon film on the students’ score of vocabulary mastery is improving. It can be seen from there was 20,72% of mean score improvement from the students’ score in the preliminary study up to the second cycle. It means that there is an improvement of cartoon film on students’ vocabulary mastery at the sixth grade of MIS Thoyyibatul Ulum Hutaimbaru in 2020/2021 Academic Year. Keyword: Cartoon Film, Vocabulary mastery